Preparation of different basic Si-MCM-41 catalysts and application in the Knoevenagel and Claisen-Schmidt condensation reactions - Martins, Leandro [UNESP]; Hoelderich, Wolfgang; Hammer, Peter [UNESP]; Cardoso, Dilson (Academic Press Inc. Elsevier B.V., 2010)
In the present work, the basicity of three different Si-MCM-41 mesoporous materials, namely, (1) as-synthesized Si-MCM-41, (2) Si-MCM-41 modified by dispersing cesium oxide (Cs(2)O) and (3) Si-MCM-41 with anchored aminopropylsilyl group was compared for the first time. The fact that Knoevenagel and Claisen-Schmidt condensations stand out to be important in carbon-carbon bond formation as well as in the preparation of fine chemicals and intermediates, led them to be used as model reactions for the purpose of evaluating the catalytic performance. The activity of the modified samples was compared with that of the as-synthesized material [CTA(+)]-Si-MCM-41 (where CTA(+) stands for the structure directing agent). This catalyst presented the highest catalytic activity compared to that of Si-MCM-41 modified with Cs(2)O or aminopropylsilyl group. This is of extreme high advantage, because it can be used as-synthesized without further modification. Furthermore, structural properties of the Si-MCM-41 samples were determined based on X-ray diffraction measurements (XRD), nitrogen adsorption/desorption isotherms, (29)Si nuclear magnetic resonance (MAS NMR) and X-ray photoelectron spectroscopy (XPS). (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Si-MCM-41; Basic catalysis; Knoevenagel condensation; Hybrid organic-inorganic mesoporous materials